Early oral switch to combined cefixime therapy for management of osteoarticular infections in pediatric sickle cell disease patients: A descriptive analysis. Issue 1 (January 2022) - Mohzari, Yahya A.; Alshuraim, Renad; Asdaq, Syed Mohammed Basheeruddin; Aljobair, Fahad; Alrashed, Ahmed; Alsowaida, Yazed Saleh; Alamer, Amnah; Al Munjem, Manea Fares; Al Musawa, Mohammed I.; Hatata, Muhannad; Alzaaqi, Meshal A.; Binrokan, Aljawharah; et al.
Abstract: Background: The treatment of osteoarticular infections in pediatric patients with sickle cell disease (SCD) is a challenging task for the practitioner. The aim of this study is to evaluate cefixime for the treatment of osteoarticular infections in pediatric SCD patients by retrospective design. Methods: This study was done in the pediatric hospital of King Saud Medical City, Riyadh, Saudi Arabia. The data was obtained from medical records of patients aged 1–16 years admitted between January 2019 to December 2020, diagnosed with SCD and received cefixime for the treatment of OI. A descriptive study for pediatric patients admitted between January 2019 to December 2020 diagnosed with sickle cell disease and diagnosed with osteoarticular infection. All patients were treated with cefixime. Medians and interquartile ranges (IQRs) were used for the descriptive analysis. Results: A total of 260 patients were screened, and 51 cases [osteomyelitis (OM), n = 43, and septic arthritis (SA), n = 8] met the inclusion criteria. The median age of OM patients was 7 years, with males making up 67.4% of the cohort. The median length of IV antibiotics and hospital stays were 10 days and 11 days, respectively. The median total duration of antibiotic use was 37 and 25 days for OM and SA, respectively. The treatment success rate was 88% in OM cases and 100% in SA patients. Readmission was noted in 39.5% of the OM patients, while only 25% of the SA patients were recorded for reinfection. Conclusion: The study's findings revealed that Cefixime is a viable oral alternative for treating osteoarticular infection in pediatric SCD patients. Nonetheless, a prospective investigation is required to corroborate the findings of this study.